The Impact of Early Marriage on Reproductive Health in Women: A Literature Review - Adha, Chyntia Nurul; Handayani, Sarah (Universitas Ibn Khaldun Bogor, 2025)
There are an estimated 650 million cases of early marriage in the world today. The East Asia and Pacific region, which includes Indonesia, has the third largest number of early marriage cases in the world, contributing around 13% of the total rateglobal early marriage. Early marriage occurs when one or both partners are under the age of 19. Early marriage has a significant impact on women's reproductive health, due to the immaturity of the reproductive system. Teenage pregnancy has significant health consequences for both the mother and the baby. This article aims to discuss the impact of early marriage on women's reproductive health, based on previous studies. In writing, this article uses the literature review method by referring to various relevant research articles. From the analysis, it is revealed that early marriage has a harmful impact on women's reproductive health. Physical immaturity and organs reproductiveincrease the risk of health problems in mothers and babies. Therefore, it is important to consider the mature age factor as one of the criteria in starting a marriage.